Challenges and opportunities for livestock Development in the highlands of Ethiopia - Sileshi, Z.; Tegegne, Azage (International Centre for Integrated Mountain Development, 2000)
The influence of man and his domestic animals has profoundly altered both the ecology and landscape of the Ethiopian highlands. Ecological degradation is one of the main challenges in this region. This paper highlights the state of the resource base, R&D investments and the scope to improve livestock research efforts, and future research directions to improve the productivity of the eco-regions.